2019
DOI: 10.5194/angeo-37-299-2019
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic models of the interplanetary magnetic field

Abstract: Abstract. Current knowledge on the description of the interplanetary magnetic field is reviewed with an emphasis on the kinematic approach as well as the analytic expression. Starting with the Parker spiral field approach, further effects are incorporated into this fundamental magnetic field model, including the latitudinal dependence, the poleward component, the solar cycle dependence, and the polarity and tilt angle of the solar magnetic axis. Further extensions are discussed in view of the magnetohydrodynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…It should be noted that many authors (e.g. Owens and Forsyth 2013 ; Lhotka and Narita 2019 ) do not refer to the general form of Equation ( 5 ), but rather its frequently used special case of constant in the limit , to wit as the ‘Parker spiral field’, with the latter authors even (wrongly) criticizing Parker’s model for not recognizing the sign reversal of the dipolar magnetic field across the two hemispheres. This sign reversal, however, is easily included by prescribing, say, , and Parker ( 1958 ) actually does mention as a possible choice to represent the solar dipole.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…It should be noted that many authors (e.g. Owens and Forsyth 2013 ; Lhotka and Narita 2019 ) do not refer to the general form of Equation ( 5 ), but rather its frequently used special case of constant in the limit , to wit as the ‘Parker spiral field’, with the latter authors even (wrongly) criticizing Parker’s model for not recognizing the sign reversal of the dipolar magnetic field across the two hemispheres. This sign reversal, however, is easily included by prescribing, say, , and Parker ( 1958 ) actually does mention as a possible choice to represent the solar dipole.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…( 3) does not include time-dependent effects, such as variations in the axial tilt or the solar cycle. However, it is based on the classical Parker spiral including the axial tilt of the solar dipole with respect to the ecliptic (Lhotka & Narita 2019). The approach is therefore only valid on secular timescales, that is, where time-dependent effects due to solar activity are canceled because of averaging.…”
Section: Lorentz Forcementioning
confidence: 99%
“…The approach is therefore only valid on secular timescales, that is, where time-dependent effects due to solar activity are canceled because of averaging. For additional information, see Lhotka & Narita (2019).…”
Section: Lorentz Forcementioning
confidence: 99%
“…The authors concluded that field lines rooted in active regions often have constant latitude out to about 0.3 AU, as predicted by the Parker model, but bend at larger distance and become approximately parallel to the ecliptic plane. No detailed comparison seems to have been undertaken so far with models including a latitudinal component of the heliospheric magnetic field, which have been developed to account for unusual magnetic connections traced by energetic particles (see the reviews by Smith, 2008;Owens and Forsyth, 2013;Lhotka and Narita, 2019).…”
Section: The Geometry Of the Heliospheric Magnetic Fieldmentioning
confidence: 99%